2013
DOI: 10.1021/jm301855r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Pyranopterin Monophosphate, a Biosynthetic Intermediate in the Molybdenum Cofactor Pathway

Abstract: Cyclic pyranopterin monophosphate (1), isolated from bacterial culture, has previously been shown to be effective in restoring normal function of molybdenum enzymes in molybdenum cofactor (MoCo)-deficient mice and human patients. Described here is a synthesis of 1 hydrobromide (1·HBr) employing in the key step a Viscontini reaction between 2,5,6-triamino-3,4-dihydropyrimidin-4-one dihydrochloride and D-galactose phenylhydrazone to give the pyranopterin (5aS,6R,7R,8R,9aR)-2-amino-6,7-dihydroxy-8-(hydroxymethyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…16 An efficient total synthesis of cPMP has recently been reported that yields material that can be enzymatically converted to mature cofactor capable of reconstituting apo sulfite oxidase. 17 …”
Section: The Molybdenum Cofactormentioning
confidence: 99%
“…16 An efficient total synthesis of cPMP has recently been reported that yields material that can be enzymatically converted to mature cofactor capable of reconstituting apo sulfite oxidase. 17 …”
Section: The Molybdenum Cofactormentioning
confidence: 99%
“…Depending on the time of treatment initiation, patients can reach an almost normal neurodevelopmental outcome [ 165 ]. Very recently, the chemical synthesis of cPMP has been reported, providing a key milestone in the clinical development of cPMP therapy [ 166 ].…”
Section: Treatment Of Mocd Type a Patients With Cpmpmentioning
confidence: 99%
“…The cPMP ( 2 ) necessary is currently being produced biotechnologically, using genetically modified E. coli developed by Schwarz et al,6,11b,13b,14a followed by HPLC purification, and storage at –80 °C 11b. Recently, the organic synthesis of labile cPMP ( 2 ) using the Viscontini reaction as the key step was reported 14b,14c…”
Section: Introductionmentioning
confidence: 99%